Color preference of trhips (thysanoptera: tripidae) in crysanthemum crops at the bogotá plateau (1989)
White, violet, yellow, red, orange and green colors with six replicates were tried. This study was done in a green housegrown chrysantemum crop. White and violet showed the highest efficiency by capturing the greatest number of adults of Frankliniella oeeidentalis, the most abundant species during the experimento Green color captured the lowest number of F. oeeidentalis. Other species captured were F. panamensis Hood,F. minuta (Moulton), F. auripes Hood and Tbrips tabaei Lindeman.